Health Inequalities Across The European Union Regions: A Beta-Convergence Approach - Jaworska, Renata (Comparative Economic Research. Central and Eastern Europe, 2014)
The European Union is currently facing a serious problem concerning the occurrence of significant health inequalities observed between particular member states as well as within these states. Substantial efforts are being made to achieve an economic and social cohesion and the reduction of health inequalities between the EU regions is an important element of this process. This work is devoted to the study of the variations of health status (measured by life expectancy) across the EU regions of NUTS II level. We apply existing tools developed in economic growth literature to study a mortality convergence. Using the idea of unconditional convergence model developed for economic growth, we can confirm a decrease or increase of regional health inequalities. The main research hypothesis is as follows: whether regions with lower initial life expectancies have experienced the largest increases in life expectancies. To verify the hypothesis of beta-convergence we use spatial econometric models which additionally allow to take the geographic dependence among the surveyed regions into consideration. Due to the heterogeneity of the surveyed spatial units we also verify the hypothesis of the club beta-convergence.